Incidental discovery of invasive lobular carcinoma and anaplastic large cell lymphoma during sentinel lymph node biopsy: a case report - Kim, Euitae (Frontiers in Oncology, 2024)
This study reports a rare case of concurrent invasive lobular carcinoma (ILC) of the breast and ALK-negative anaplastic large cell lymphoma (ALCL) detected during sentinel lymph node biopsy (SLNB). A 55-year-old female underwent breast cancer surgery following abnormal breast screening results, revealing ILC histologically. Unexpectedly, SLNB identified ALCL, later confirmed on pathology. The patient received no ALCL-specific treatment due to lack of additional lesions and remained recurrence-free post-surgery. The paper discusses diagnostic challenges, emphasizing comprehensive evaluation and multidisciplinary collaboration. It highlights the rarity of simultaneous ALCL and breast cancer without prior radiation, stressing the importance of clinical vigilance. Despite challenges in differentiation and treatment optimization, individualized patient care is crucial. Further research into concurrent ALCL and breast cancer is essential for improved management strategies. This case underscores complexities in managing rare malignancies and emphasizes the need for tailored approaches for optimal patient outcomes.